Identification and environment-friendly biocontrol potential of five different bacteria against Aphis punicae and Aphis illinoisensis (Hemiptera: Aphididae) - Baazeem, Alaa; Alotaibi, Saqer S.; Khalaf, Luaay Kahtan; Kumar, Uttam; Zaynab, Madiha; Alharthi, Sarah; Darwish, Hadeer; Alghamdi, Akram; Jat, Suresh Kumar; Al-Barty, Amal; Albogami, Bander; Noureldeen, Ahmed; et al. (Frontiers in Microbiology, 2022)
Entomopathogenic nematodes (EPN) / bacterium symbiotic associations have long been used as biocontrol tools for insect pests. In Saudi Arabia's Taif region, there have only been a few reports of such organism. The current work aimed at to isolate and identify new EPB strains associated with Steinernema feltiae, and to assess the EPB's biocontrol potentialon Aphis punicae and Aphis illinoisensis adults in the laboratory. From S. feltiae, five bacterial isolates were isolated and molecularly characterized. They are: Xenorhabdus sp.; Lysinibacillus xylanilyticus strain BN-13; Serratia liquefaciens strain Bp-27; Stenotrophomonas maltophilia strain G10b; and Pseudochrobactrum saccharolyticum strain XLX1. Pathogenicity tests demonstrated that bacterial cells were more toxic against the two aphid species than bacterial cell-free supernatants. S. maltophilia strain G10b cells and filtrate were reported to have the strongest potential to kill A. punicae and A. illinoisensis individuals within 6 h after treatment, with 100% mortality of both insects 24 and 48 h after treatment. According to the study's findings, the direct application of endogenous Steinernema-associated EPB as a biocontrol agent for A. punicae and A. illinoisensis looked promising.